Pitch, Formant Frequencies, Intensities as Speech Cue to preceived age (International Journal of Engineering and Computer Science, 2018)
Voice of a person gives an idea regarding the age, gender and health of a person. In this paper we tried to have an idea about the age of speaker.  Our study includes 30 speakers of 14-30, 31-49, 50-80 age groups. we have considered different voice parameters fundamental frequency F0 , formant frequencies F1, F2, F3, F4 and intensities. In this different voiced vowels are used to study the changes  between  the  three age groups